Investigating household energy conservation behaviours in Johannesburg, South Africa - Williams, Stephanie (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
Behavioural change is increasingly anticipated as an important pathway towards the reduction of the human footprint on the environment. Monitoring resource consumption at the household scale is essential as a basis for evaluating current performance and supports the understanding of how behaviour change interventions can be implemented. Yet, there are comparatively fewer studies on pro-environmental behaviour (PEB) in developing country contexts than in developed countries. Further, where research efforts have been made in developing countries, these have mainly focussed on low-income households. This means the extant literature on PEB is limited across a geographic and economic gradient, making generalisations about PEB problematic and limiting the scope for thinking about interventions for promoting pro-environmental behaviour in developing countries. In response to this, the study focuses on high-income households in Johannesburg, South Africa. Overall, the findings show a high level of heterogeneity in reported pro-environmental energy use behaviour, attributed to a suit of socio-demographic and value factors. Mainly, age, number of dependents, household size. Valuing leisure time were negatively correlated to energy use behaviours, while valuing environmental quality positively correlated to energy use behaviours. The provision of information energy-saving interventions yielded positive behavioural change as shown by reduced energy consumption of up to 12% in the Treatment group. However, no significant correlations were found between energy reduction and socio-demographic and personal value factors, which can be attributed to a different cultural context. The study discusses the implications of the findings on debates around pro-environmental behaviour and factors influencing pro-environmental behaviour, and provides further recommendations for future energy policies related to the household sector.
Keywords: Environmental behavior -- South Africa; Energy conservation -- Psychological aspects -- South Africa; Energy consumption -- Psychological aspects -- South Africa; South Africans -- Energy consumption